The Relative Contribution of Resilience and Social Support to Family Quality of Life of a Sample of Mothers of Children with Autism Spectrum Disorder in Qatar - Elsayed Elshabrawi A. Hassanein; Taha Rabie T. Adawi; Asma Abdullah Al-Attiyah; Walid Atef Mansour Elsayad (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: This research aims to explore the family quality of life, resilience, and social support of mothers of children with an autism spectrum disorder in Qatar. Additionally, it aims to investigate the relationship between the family quality of life, resilience, and social support, and the possibility of predicting the family quality of life through resilience and social support. Methods: The current research utilizes the descriptive approach on the sample of (220) mothers of children with an autism spectrum disorder. Three tools were utilized in this research: The Family Quality of Life scale, the Brief Resilience scale, and the Social Support scale. Results: The results show that the participants obtained a high level in most aspects of family quality of life and social support, while they obtained a medium level in resilience. The results of the current research also revealed a positive relationship between family quality of life and both resilience social and support, and the possibility of predicting family quality of life through social support. Conclusions: The current study concluded that social support and resilience are very importance in enhancing the quality of family life.